Conservative Management of Unset Mineral Trioxide Aggregate Root-End Filling: A Case Report - Parirokh, Masoud; Farzaneh, Sedigheh; Halajmonfared, Ali Reza (Iranian Endodontic Journal, 2016)
This case report presents conservative management of unset mineral trioxide aggregate (MTA) after being placed as a root-end filling material following periapical surgery. Periapical surgery was indicated for a maxillary lateral incisor of a 15-year-old male due to persistent exudate and a large periapical lesion. During surgery Angelus MTA was placed as root-end filling. The next session it was noticed that MTA had failed to completely set. In an orthograde approach, calcium-enriched mixture (CEM) cement was used to obturate the root canal space. The patient was followed up for 27 months and did not exhibit any clinical signs and symptoms. Radiographic images showed complete healing of the lesion. Keywords: Calcium-Enriched Mixture; Calcium Silicate; CEM Cement; Dens Invaginatus; Mineral Trioxide Aggregate